CSR Activities Conducted by Corporate India - Peswani, Shilpa; Ramesh, G. (SFIMAR Research Review, 2019)
'Over the years, Corporate Social Responsibility (CSR) has gained wider implications than mere philanthropy. This paper attempts to identify contribution of listed Indian companies towards CSR activities based on the norms and regulations prescribed by the Company’s Act 2013. It also attempts to identify the most preferred CSR activity among the activities listed by the Government based on the CSR expense incurred by the companies. The authors have provided the findings and recommendations on the basis of descriptive and inferential analysis of their study of listed companies.